2005
DOI: 10.1016/j.cub.2005.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Giant Larvae Controls the Localization of Notch-Signaling Regulators Numb, Neuralized, and Sanpodo in Drosophila Sensory-Organ Precursor Cells

Abstract: Asymmetric distribution of fate determinants is a fundamental mechanism underlying the acquisition of distinct cell fates during asymmetric division. In Drosophila neuroblasts, the apical DmPar6/DaPKC complex inhibits Lethal giant larvae (Lgl) to promote the basal localization of fate determinants. In contrast, in the sensory precursor (pI) cells that divide asymmetrically with a planar polarity, Lgl inhibits Notch signaling in the anterior pI daughter cell, pIIb, by a yet-unknown mechanism. We show here that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
98
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 30 publications
10
98
1
Order By: Relevance
“…In Drosophila neuroblasts of the SOPs, Lgl is important in the asymmetric distribution of Numb (Betschinger et al, 2003;Wirtz-Peitz et al, 2008), an inhibitor of Notch signalling. Indeed, SOP cells have ectopic Notch signalling (Langevin et al, 2005;Roegiers et al, 2005). Similarly, the neural tube of lgl1 À/À mice displays hyperplasia that is associated with increased Notch signalling (Klezovitch et al, 2004).…”
Section: Scribble/dlg/lgl and Other Polarity Complexesmentioning
confidence: 99%
“…In Drosophila neuroblasts of the SOPs, Lgl is important in the asymmetric distribution of Numb (Betschinger et al, 2003;Wirtz-Peitz et al, 2008), an inhibitor of Notch signalling. Indeed, SOP cells have ectopic Notch signalling (Langevin et al, 2005;Roegiers et al, 2005). Similarly, the neural tube of lgl1 À/À mice displays hyperplasia that is associated with increased Notch signalling (Klezovitch et al, 2004).…”
Section: Scribble/dlg/lgl and Other Polarity Complexesmentioning
confidence: 99%
“…Mouse mutants lacking the mammalian form of Lgl, a protein linked to Numb distribution in Drosophila (Langevin et al 2005), develop structures similar to primitive neuroectodermal tumors and severe hydrocephalus, and die neonatally (Klezovitch et al 2004). The vast majority of Lgl1 −/− progenitors fail to distribute the Numb polarity protein asymmetrically and undergo hyper-proliferation, resulting in "cortical dysplasia."…”
Section: Polarity Proteins In Neurogenesismentioning
confidence: 99%
“…Spdo, a fourpass transmembrane protein involved in N signaling in Drosophila, is regulated by endocytosis in the SOPs (20,24,(45)(46)(47). Quantification of cortical versus cytoplasmic signals of Spdo showed that in wild-type NBs, Spdo was primarily cytoplasmic at metaphase, and it displayed weak cortical localization in the NB but not IPs at telophase ( Fig.…”
Section: Inactivation Of Ap-2 Complex Subunits Resulted In Ectopicmentioning
confidence: 99%